ENFORCEMENT OF STATE FEES IN ECONOMIC COURTS: A COMPARATIVE LEGAL ANALYSIS - Jasur Nuriddinov Rukhiddin O’g’li (International Journal of Business, Law and Political Science, 2024)
Objective: Evaluate the state duty system in economic courts in Uzbekistan, with a focus on its impact on the affordability and accessibility of legal services. The study explores the financial barriers that individuals and businesses, particularly small and medium-sized enterprises (SMEs), face when navigating economic disputes in the judicial system. Method: The study employs a comparative-legal approach, utilizing logical, empirical, and specific scientific methods tailored to legal studies. It involves analyzing existing legal frameworks through comparison with practices in neighboring countries, such as Russia and Kazakhstan, using both qualitative and quantitative analysis to understand the differences in state duty structures and enforcement mechanisms. Results: The current state duty system in Uzbekistan is significantly higher than in neighboring countries, creating financial burdens for SMEs and individuals. The research reveals that while economic courts are essential for ensuring justice, the high state fees, coupled with a lack of flexibility in fee structures, make access to justice more difficult, particularly for smaller businesses. The study suggests potential reforms, such as introducing caps on state fees and adopting more flexible fee structures similar to those in Russia and Kazakhstan, which could improve accessibility and fairness. Novelty: This research offers a unique contribution by comparing Uzbekistan’s economic court fee structure with those of neighboring countries, providing insights into the potential benefits of adopting foreign legal practices to enhance judicial accessibility. Additionally, it presents practical recommendations for reforming the state duty system, a topic that has been relatively underexplored in the context of post-Soviet legal systems.